Shades and Tactics of the Precariousness in the Contemporary Chilean University - Fardella, Carla; Broitman, Claudio (Cuadernos de Relaciones Laborales, 2024)
Precariousness, uncertainty, and instability are constitutive parts of the academic profession in the contemporary university. Based on the discursive analysis of 70 interviews with academics in different working conditions, we describe disruptions, experiences, and management around the precariousness of a labor scenario that encourages individualism, competition, and entrepreneurship in the university. The results show a discomfort that coexists with creative ways to generate stability in the academic career, contributing to make visible the different expressions of precariousness in this context.